Manajemen Komunikasi Krisis Desa Wisata Pulesari dalam Menghadapi Pandemi Covid-19 - Yani Tri Wijayanti (JCommsci - Journal Of Media and Communication Science, 2022)
The Covid-19 Pandemic that has hit Indonesia for the last two years has had an impact on all sectors of life, including the tourism sector. The impact is felt in the tourist villages, one of which is Pulesari Tourism Village. A very significant decline in tourist visits since March 2020, even having to close for a few months, has an impact on the economic condition of the surrounding community, because this tourist village is managed by the community themselves. The Pandemic is one of the causes of the crisis. This study aims to find out how tourism village crisis communication management is in the face of the covid-19 pandemic. the well as analysis of crisis management, the right strategy is an adaptive strategy. For crisis communication management, there are three main principles in crisis communication, namely speed of conveying messages, consistency, and openness. Crisis communication management can be done by tourism village managers is by developing communication strategies, delivering messages regularly, optimizing communication channels by utilizing social media, and providing input to policymakers.